Monetary Policy and Corporate Behavior in India. (IMF Working Papers; Working Paper, 2005)
The paper examines the association and corporate behavior for a sample of manufacturing firms in India for the post-reform period 1992-2003. The findings suggest that a contractionary monetary policy lowers overall debt including bank debt, although the lagged response is positive, and listed firms increase their short-term bank borrowings, after monetary tightening. The responses of corporates to a monetary contraction in the post-1997 period has been more pronounced. A disaggregated analysis of responses of firms according to size and leverage largely validates these findings. Two policy implications emerge from the analysis. First, the interest rate transmission channel has strengthened since 1998, and, second, corporates in India, especially listed ones, seem to exhibit relationship lending.